Prevalence and Clinicopathologic Features of HER2 Overexpression in Endocervical Adenocarcinoma - Niusha Momeni; Fatemeh Nili; Fereshteh Ameli; Soheila Sarmadi; Elham Mirzaian; Farnaz Moravej-Salehi; Narges Zamani (Middle East Journal of Cancer)
Background: Endocervical adenocarcinoma (ENCA) has poor prognosis and is increasing in developing countries. Human epidermal growth factor receptor 2 (HER2) overexpression in ENCA is not fully known. The aim of this study was to assess the prevalence and clinicopathological features of HER2 overexpression in ENCA.Method: In this cohort study, 48 ENCA cases were reclassified using the World Health Organization (WHO) classification. Whole-tissue sections were stained for HER2 by immunohistochemistry (IHC) and scored using 2017 American Society of Clinical Oncology/College of American Pathologists (ASCO/CAP) protocol (negative= 0, 1+, equivocal= 2+, and positive= 3+). Fluorescent in situ hybridization (FISH) assay was performed for 2+ stained cases. Invasion growth pattern and clinicopathologic features were investigated. Statistical analysis was performed using Statistical Package for Social Sciences (SPSS) and Statistical software for data science (STATA) with chi square, Fischer exact, independent sample t-test, and one-way Analysis of Variance (ANOVA) at 0.05 significance level.Results: 16.6% of ENCAs overexpressed HER2, IHC3+ (n=6) and IHC2+ (n=2). No human papilloma virus (HPV)-independent case was found. HER2 was expressed in half of the invasive stratified mucin-producing carcinomas (ISMICs) (P < 0.05) and was not associated with stage, metastasis, lymph-vascular space invasion, lymph node metastasis, or pattern of invasion (P > 0.05). Conclusion: ENCAs, including HPV-associated subtypes, overexpress HER2 in about 16.6% of the cases. Overexpression in ISMIC is significantly higher than the other subtypes, which can be considered for therapeutic trials in this histopathologic subcategory.